Estetika dan Identitas Islam Jawa dalam Arsitektur Masjid Raya Ulul Albab UIN Sunan Ampel Surabaya - Munir, Misbahul (Postgraduate Studies UIN Sunan Ampel Surabaya, 2023)
The mosque serves not only as a place of worship but also as a center for social and religious education among Muslims. Historically, mosque architecture in the Indonesian archipelago reflects a strong process of acculturation between Islamic values and local traditions, particularly Javanese culture. This study seeks to explore the meaning of local Islamic architecture in the Ulul Albab Grand Mosque of UIN Sunan Ampel Surabaya as a representation of the interaction between Islam and Javanese wisdom. The research focuses on the historical background of the mosque’s construction, spatial structure, and architectural symbolism that embodies the identity of Javanese Islam. This study employs a qualitative method with a descriptive-analytical approach, supported by literature studies and interviews to deepen the interpretation of symbolic meanings. The findings reveal that architectural elements such as the earthen foundation, tiered tajug roof, mustaka (finial), and bedug (drum) contain philosophical values rooted in Javanese cosmology and spirituality. The architectural form of the Ulul Albab Grand Mosque not only presents the aesthetics of local Islamic art but also articulates a harmonious relationship between religiosity, culture, and sacred space. Hence, the mosque stands as a tangible symbol of the integration of Islamic values and Javanese local wisdom within the broader framework of Islamic civilization in the Indonesian archipelago.